Dynamics and Stability Mechanism of Lactoferrin–EPA During Emulsification Process: Insights from Macroscopic and Molecular Perspectives - Han Tao; Wei Ding; Meng-Jia Fang; Hao Qian; Wan-Hao Cai; Hui-Li Wang (Foods)
Although eicosapentaenoic acid (EPA) as a functional fatty acid has shown significant benefits for human health, its susceptibility to oxidation significantly limits its application. In this study, we developed a nanoemulsion of the lactoferrin (LTF)–EPA complex and conducted a thorough investigation of its macro- and molecular properties. By characterizing the emulsion with different LTF concentrations, we found that 1.0% LTF formed the most stable complex with EPA, which benefited the formation and stability of the emulsion against storage and freezing/thawing treatment. As the foundation block of the emulsion structure, the binding mechanism and the entire dynamic reaction process of the complex have been fully revealed through various molecular simulations and theoretical calculations. This study establishes a comprehensive picture of the LTF–EPA complex across multiple length scales, providing new insights for further applications and productions of its emulsion.